Community Participation in Tourism Development at the Macaronis Tourism Attraction, Silabu Beach, Mentawai Islands - Saputra, Nika; Syamsir, Syamsir; Embi, Muhamad Ali; Mulia, Rizki Afri (STIA Adabiah, 2023)
This research aims to describe the participation of the Silabu community in tourism development at the Macaronis tourist attraction on Silabu Beach, Mentawai Islands. This type of research is descriptive-qualitative, the research subjects were chosen using purposive sampling, with the criteria for the research subjects being the local government and some members of the community. The techniques and data collection used are literature study and field study. Based on the research results, it was found that the participation of the Silabu community in developing the Macaronis tourist attraction was very instrumental in the establishment of this tourist attraction. Starting with proposing policies and hopes from the community for the development of the Macaronis tourist attraction area. Community participation in the field of facilities and infrastructure is something that has a big influence. The community as a workforce is the spearhead of a job, especially for this tourist spot, which requires quite a lot of energy, hard work, skills, and abilities. The obstacles encountered in developing tourism at the Macaronis Beach Silabu tourist attraction in the Mentawai Islands are that some participants have a top-down participation type or forced participation type, limited accessibility, especially land road access, availability of facilities and infrastructure, especially parking areas and counters in the Macaronis tourist attraction area, as well as limited human resources, both people employed and skills and abilities that still need to be improved, especially in service. Efforts made to overcome obstacles in developing tourism at the Macaronis Beach Silabu tourist attraction in the Mentawai Islands are in terms of community participation motivating each other to participate, in terms of limitations and availability of accessibility, facilities, and infrastructure, the efforts made are that the government continues to negotiate with superiors for an additional budget for improving access and completing facilities and infrastructure at the Macaronis tourist attraction.